Answer:
x=2,3
Step-by-step explanation:
(x- 2) (x - 3) =0
Using the zero product property
x-2 =0 x-3 =0
x-2+2=0+2 x-3+3 =0+3
x=2 x+3
system of equations algebraically are shown in the table.
y = -x2 +2x - 9
y = -6x + 6
(5,-24) and (3, -12)
(5,36) and (3, 24)
(-5, -24) and (-3, 12)
(-5, 36) and (-3, 24)
Step
Equation
-x² + 2x -9 = -6x + 6
0 = x2 – 8x+15
0 = (x - 5)(x-3)
2
Mark this and retum
Save and Exit
Sumber
ere to search
te
g
Answer:
(3,-12) and (5,-24)
Step-by-step explanation:
Given the system of two equations
Equate right sides of these two equations:
Rewrite this equation:
If x=3, then
If x=5, then
You get two solutions (3,-12) and (5,-24)
The solution set of the system of equation is (5, -24) and (3, -12)
The given systen of equation is one linear and one quadratic. Given the syatem of equations
Equating bothequations will give
Equate to zero
Factorize
Recall that ;
y = -6x + 6
If x = 5
y = -30 + 6
y = -24
If x = 3
y =-6(3) + 6
y = -12
Hence the solution set of the system of equation is (5, -24) and (3, -12)
Learn more on system of equation here: brainly.com/question/25976025
#SPJ5
I agree with choosing the mode
Answer:
Impossible. He needs 10 more trees.
Step-by-step explanation:
10=5*2
10≠5*4
20≠5*2
20=5*4
Answer:
2.4
Step-by-step explanation:
12672/5280